1992
DOI: 10.1111/j.1600-0447.1992.tb03280.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone density and major hormones regulating calcium metabolism in anorexia nervosa

Abstract: Bone density of lumbar vertebrae (L2 to L4) and the whole body in 29 patients with anorexia nervosa were measured by dual photon absorptiometry, and the results were compared with those of 10 age-matched normal controls. The patients had significantly lower bone mineral density (BMD) in L3 and L2-4 than controls. However, there was no difference in whole-body BMD. L3 and L2-4 BMD was positively correlated with body weight and was negatively correlated with duration of illness and amenorrhea. Patients who had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 26 publications
3
32
0
1
Order By: Relevance
“…Soyka et al examined mechanisms of bone loss in adolescents with AN and found similar serum 25OHD concentrations among 19 adolescent girls with AN and 19 controls [4]. Kiriike et al found that among 29 patients with AN, most had normal vitamin D concentrations (defined as 25OHD >16 ng/mL) [9]. Another study of 12 patients with AN found no significant difference in the serum 25OHD level between patients and controls [10].…”
Section: Introductionmentioning
confidence: 99%
“…Soyka et al examined mechanisms of bone loss in adolescents with AN and found similar serum 25OHD concentrations among 19 adolescent girls with AN and 19 controls [4]. Kiriike et al found that among 29 patients with AN, most had normal vitamin D concentrations (defined as 25OHD >16 ng/mL) [9]. Another study of 12 patients with AN found no significant difference in the serum 25OHD level between patients and controls [10].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in bone mineral density (BMD) is frequently seen in patients with anorexia nervosa (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and these patients have a higher incidence of fractures compared with healthy young women (13)(14)(15). Although both prospective and follow-up studies have been performed to investigate the risk factors for osteoporosis in anorexia nervosa, in which metacarpal index, single-and dual-photon absorptiometries or quantitative computed tomography have been used to measure BMD (1,2,5,9,11,12,(16)(17)(18)(19)(20), the conclusions regarding the risk factors for osteoporosis remain controversial (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Although both prospective and follow-up studies have been performed to investigate the risk factors for osteoporosis in anorexia nervosa, in which metacarpal index, single-and dual-photon absorptiometries or quantitative computed tomography have been used to measure BMD (1,2,5,9,11,12,(16)(17)(18)(19)(20), the conclusions regarding the risk factors for osteoporosis remain controversial (5)(6)(7)(8)(9)(10)(11)(12). Several longitudinal studies have revealed different recovery patterns of low BMD in the clinical course of anorexia nervosa patients complicated with osteoporosis (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that binge eating and purging behavior could reduce BMD (Baker, Roberts, & Towell, 2000). However, others found no relation between binge eating/purging behavior and BMD (Iketani et al, 1995;Kiriike et al, 1992). In consideration of these factors, we decided to rule out AN-BP patients in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with AN have severe emaciation due to decreased food intake secondary to abnormal eating behavior and the pursuit of thinness. AN patients often suffer from physical complications, such as osteopenia and osteoporosis, and often incur pathologic fractures of the hip and/or spine (Brotman & Stern, 1885;Kaplan, Pertschuk, Fallo, & Haddad, 1986;Kiriike et al, 1992;Maugars et al, 1996;Mehler, 2003;Rigotti, Nussbaum, Herzog, & Neer, 1984). The cause of decreased bone mineral density (BMD) in patients with AN is controversial.…”
Section: Introductionmentioning
confidence: 99%